GAMBARAN KEJADIAN DAN MANAJEMEN DISMENORE PADA REMAJA PUTRI DI KECAMATAN LIMA PULUH KOTA PEKANBARU - Anisa Wulandari; Oswati Hasanah; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Dysmenorrhea is characterized by lower abdominal pain, with the level of pain vary ranging from mild to severe and management of dysmenorrhea can be used with several ways, such as pharmacological, non-pharmacoloical and combined. The purpose of this research was to determine the description level of pain and management dysmenorrhea among female students in Subdistrict Lima Puluh Pekanbaru, with quantitative research and descriptive design. Population in this research was female students in Junior High School at Subdistrict Lima Puluh Pekanbaru with sample of 208 respondents are taken based on inclusion criteria. The instrument in this research used is numerical rating scale for the variable of pain level and the questionnaire for the variable of management dysmenorrhea. The result of this research most respondents experience dysmenorrhea with moderate pain (48,1%). Majority management of dysmenorrhea with non-pharmacological (91,8%) are used most of female students with taking rest (96,6%) and ignore the pain (76,9%). In this research suggest to female students who have experience dysmenorrhea to do the right management, so that the pain does not interfere with school activities. Keywords: dysmenorrhea, female students, management dysmenorrhe